Saving a semester of learning: MIT's emergency transition to online instruction. Issue 7 (15th June 2020) - Kessler, Aaron; Barnes, Sheryl; Rajagopal, Krishna; Rankin, Janet; Pouchak, Lauren; Silis, Mark; Esser, Wesley
Abstract : Purpose: Prior to March 4th, 2020 only a handful of MIT courses had ever been delivered exclusively online. The purpose of this paper is to detail how over a 25-day period (March 4th-March 30th) approximately 1, 250 spring term courses transitioned to being remote online offerings in response to the COVID-19 pandemic. Throughout that time five groups on MIT's campus – the Office of Open Learning (OL), the Office of the Vice Chancellor (OVC), including in particular the Teaching + Learning Lab (TLL), Information Systems and Technology (IS&T) and Sloan Technology Services (STS) - were primarily responsible for supporting the transition of residential courses to remote online delivery. Design/methodology/approach: Together these groups were able to engage in new communication processes and collaborations, initially established by the university's Academic Continuity working group, to address three: support all faculty and instructors in transforming residential courses to remote online instruction, support all students in transitioning to remote online learning, and support teaching assistants as they transitioned to online instruction. Findings: This paper describes the organizational structure (both distributed and centralized) that allowed for such collaborations. Critical decisions made by the group are described and connected with the key goals they addressed. Finally, examples of specific tools and supports that were implemented during the transition period are highlighted. Originality/value: Certain factors existed to allow MIT to make such a massive instructional transition (e.g. scaled lecture capture capabilities, members of the digital learning lab embedded within a number of departments and an extensive library of previously created open and free online resources), the overarching process and decisions presented within are likely to resonate across institutions. The potential impact of these changes and future community opportunities are also discussed.